THE ARMENIAN QUESTION ON THE EVE OF THE RUSSO-TURKISH WAR FROM 1877 – 1878 AND ITS PLACE IN THE POST-WAR PLANS OF THE RUSSIAN GOVERNMENT - Papoyan , Diana (Revista Inclusiones, 2020)
This article is intended to present and analyse the condition of the Armenian Question on the eve of the Russo-Turkish War from 1877–1878 and its place in the Russian foreign policy. The deeper insight and interpretation of this initial phase of the internationalization of the Armenian Question is to allow a more regular assessment of the reasons due to which Saint Petersburg – a traditional defendant of Christianity within the Ottoman Empire, followed a generally neutral and indifferent position towards the repressive policy of the Sublime Porte regarding the Armenians within the Empire. As a whole, the Russian policy towards Armenia can be defined as hesitant, inconsistent, and indecisive. This problem lacks a clear governmental programme; there are multiple and different views in the political circles of the country in connection to the nature of the Russian interests in Armenia. The accurate rationalization of the foreign political strategy of Saint Petersburg in this region has to take into account that the Armenian Question has always taken a secondary place in its Near East policy compared to the questions concerning the Balkan region. To a great extent, this circumstance is the reason for the Russian attitude towards the Armenian Question not to exceed the strictly diplomatic spaces, i.e., the Armenian Question appears to be an object of a pure diplomacy lacking foreign political or military factors.